Penerapan Model PBL Berbantuan Media Video Untuk Meningkatkan Kemandirian dan Prestasi Belajar Materi Keberagaman Kelas XII SMKN 1 Delang Kabupaten Lamandau - Petrus Nekong (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
This research aims to enhance the independence and learning achievement of 12th grade students at SMKN 1 Delang by applying the Problem-Based Learning (PBL) model supported by video media. The research utilized Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of several stages namely planning, implementation, observation and reflection. The subjects of this research are 12th grade students of SMKN 1 Delang. The instruments used in this study were tests and observation sheets. The findings indicate an increase in independence from 25,92% in the first cycle to 42% in the second cycle, coupled with an improvement in classical completeness of learning achievement from 25,93% in the first cycle to 53% in the second. Based on these results, it can be concluded that the application of the PBL model supported by video media can improve learning outcomes in diversity material. On the basis of this research, the researcher suggests the following: (1) The application of the problem-based learning model supported by video media can be used in other learning materials. (2) This research needs to be followed up with other innovative and creative media so that students are motivated and interested in learning.